Pathogen-Reactive T Helper Cell Analysis in the Pig - Ebner, Friederike; Schwiertz, Patrycja; Steinfelder, Svenja; Pieper, Robert; Zentek, Jürgen; Schütze, Nicole; Baums, Christoph G.; Alber, Gottfried; Geldhof, Peter; Hartmann, Susanne (Frontiers in Immunology, 2017)
There is growing interest in studying host-pathogen interactions in human-relevant large animal models such as the pig. Despite the progress in developing immunological reagents for porcine T cell research, there is an urgent need to directly assess pathogen-specific T cells – an extremely rare population of cells, but of upmost importance in orchestrating the host immune response to a given pathogen. Here we established that the activation marker CD154 (CD40L), known from human and mouse studies, identifies also porcine antigen-reactive CD4+ T lymphocytes. CD154 expression was upregulated early after antigen encounter and CD4+CD154+ antigen-reactive T cells co-expressed cytokines. Antigen-induced expansion and autologous restimulation enabled a time- and dose-resolved analysis of CD154 regulation and a significantly increased resolution in phenotypic profiling of antigen-responsive cells. CD154 expression identified T cells responding to staphylococcal Enterotoxin B (SEB) superantigen stimulation as well as T cells resonding to the fungus Candida albicans and T cells specific for a highly prevalent intestinal parasite, the nematode Ascaris suum during acute and trickle infection. Antigen-reactive T cells were further detected after immunization of pigs with a single recombinant bacterial antigen of Streptococcus suis only. Thus, our study offers new ways to study antigen-specific T lymphocytes in the pig and their contribution to host-pathogen interactions.